Jepang Lebih Dekat: Menumbuhkan Minat Bahasa Jepang Melalui Budaya - Husna, M.Pd, Lailatul; Sutiyarti, Ulfah; Dewandono, Wiranto Aji; Emaliana, Ive (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service aims to introduce the language and culture of Japan to the students of SMA Negeri 1 Kepanjen and SMK PGRI Wlingi. After the implementation of the Independent Curriculum as a replacement for the 2013 Curriculum, Japan language teachers faced a new challenge, namely the reduction of Japan language lesson hours in schools. This service activity began with a discussion with teachers at SMA Negeri 1 Kepanjen and SMK PGRI Wlingi and to achieve this goal, the team will make students at the school the target of their activities. It is hoped that later the specialization of foreign languages, namely Japan as one of the subjects to be studied, will increase. In addition, this Community Service intends to promote the Japan Language Education Study Program of the Department of Language Education FCS UB to the wider community. The method of implementing this Community Service is by using knowledge transfer from lecturers and students to the target. This Community Service activity was carried out on June 7, 2024 at the multimedia room of SMK PGRI Wlingi and on July 26, 2024 at the Hall of SMAN 1 Kepanjen. The form of PenMas activities this time is 1) Introduction to the Japan Language Education Study Program at Brawijaya University 2) Introduction to Japan Culture 3) Introduction to college scholarships 4) Tutorial on using chopsticks 5) Introduction to Karaoke Culture in Japan. Based on the results of the questionnaire that has been distributed to students and has been analyzed based on a definite formula, it can be concluded that this service activity is considered quite effective to increase students' motivation to learn Japan.